Quercetin Preserves β-Cell Mass and Function in Fructose-Induced Hyperinsulinemia through Modulating Pancreatic Akt/FoxO1 Activation. (27th February 2013) - Li, Jian-Mei; Wang, Wei; Fan, Chen-Yu; Wang, Ming-Xing; Zhang, Xian; Hu, Qing-Hua; Kong, Ling-Dong
Abstract : Fructose-induced hyperinsulinemia is associated with insulin compensative secretion and predicts the onset of type 2 diabetes. In this study, we investigated the preservation of dietary flavonoid quercetin on pancreatic β -cell mass and function in fructose-treated rats and INS-1 β -cells. Quercetin was confirmed to reduce serum insulin and leptin levels and blockade islet hyperplasia in fructose-fed rats. It also prevented fructose-induced β -cell proliferation and insulin hypersecretion in INS-1 β -cells. High fructose increased forkhead box protein O1 (FoxO1) expressions in vivo and in vitro, which were reversed by quercetin. Quercetin downregulated Akt and FoxO1 phosphorylation in fructose-fed rat islets and increased the nuclear FoxO1 levels in fructose-treated INS-1 β -cells. The elevated Akt phosphorylation in fructose-treated INS-1 β -cells was also restored by quercetin. Additionally, quercetin suppressed the expression of pancreatic and duodenal homeobox 1 (Pdx1) and insulin gene (Ins1 and Ins2) in vivo and in vitro . In fructose-treated INS-1 β -cells, quercetin elevated the reduced janus kinase 2/signal transducers and activators of transcription 3 (Jak2/Stat3) phosphorylation and suppressed the increased suppressor of cytokine signaling 3 (Socs3) expression. These results demonstrate that quercetin protects β -cell mass and function under high-fructose induction through improving leptin signaling and preserving pancreatic Akt/FoxO1 activation.